Prevalence of avian polyomavirus in psittacine birds in the Klang Valley - Zanon, Zamir; Zainal Abidin, Nurulhuda Najihah; Abu, Jalila; Abdul Razak, Mariatulqabtiah (Universiti Putra Malaysia Press, 2018)
Avian polyomavirus (APV) primarily affects young birds and can cause mortality in a wide range of psittacine birds. This is the first study to detect the presence of APV in Malaysia. A total of 85 faecal samples were collected from symptom-free psittacines species from four different breeders in the Klang Valley. Upon genomic DNA extraction, the presence of APV was analysed by PCR using primers APVfull-AF (5'- ACAATGCCTAACGGAACGCC-3') and APVfull-AR (5'-CACCGAAGCGGCGATACTATA-3'). Positive results of 3 kbp PCR amplicon were detected in six out of the 30 samples (20%), which were from yellow-collared macaws, blue-headed parrots, red-crowned macaws, sulphur-crested cockatoos, blue-throated macaws, and Pesquet's parrots. As a conclusion, the prevalence of APV was clearly indicated.